Genetic Variability, Heritability and Correlation Studies in F2 Populations of Upland Cotton: Intra hirsutum F2 Population of Upland Cotton - Baloch, Muhammad Jurial; Lochi, Rehana; Jatoi, Wajid Ali; Baloch, Abdul Wahid; Arain, Muhammad Ahmed (Biological Sciences - PJSIR, 2018)
A field experiment was conducted at the experimental area of the Department of Plant Breeding & Genetics, Sindh Agriculture University Tandojam, during the year 2014-2015 in order to carry-out genetic analysis in F2 populations of upland cotton. The trial was laid-out in a Randomized Complete Block Design with four replications. The material was consisted of eight parents and ten F2 populations. The analysis of variance revealed significant differences among the parents and F2 populations for all the traits studied except that fibre length was non-significant in parents. The results further suggested that maximum heritability, higher genetic variances coupled with more genetic gains were expressed by the F2 populations CRIS-134 ´ CRIS-508 and CRIS-134 ´ CIM-598 for 1st sympodial node number; CRIS-134 ´ Neelum- 121 and CRIS-134 ´ CRIS-508 for sympodial branches/plant; CRIS-342 ´ FH-113 for boll weight; CRIS- 342 ´ Neelum-121 for bolls/plant, seed cotton yield/plant, lint % and micronaire value and progenies CRIS-342 ´ MNH-886 followed by CRIS-342 ´ Neelum-121 for staple length. These results also suggested that a number of F2 populations indicated their potential for various seed cotton yield and fibre traits. The phenotypic correlations revealed that most of the traits were significantly and positively associated with seed cotton yield/plant. However, higher correlations of sympodial branches/plant (r = 0.69**) and bolls/ plant (r = 0.82**) with seed cotton yield indicated that both the traits are more reliable as compared to other traits for selection of higher seed cotton yields. Very interestingly, fibre traits like lint%, fibre length and micronaire were also significantly correlated with seed cotton yield, suggesting that fibre quality traits can be improved without compromising on seed cotton yield. Thus, the material under study is very promising and worthy of selection to improve many traits simultaneously.